A Model of Job and Worker Flows - Kiyotaki, Nobuhiro; Lagos, Ricardo (Journal of Political Economy, 2007)
We develop an equilibrium search model that incorporates job‐to‐job transitions, exhibits instances of replacement hiring, and conceptually distinguishes between job and worker flows. We propose a notion of competitive equilibrium for random‐matching environments and study the extent to which it achieves an efficient allocation of resources. The model can be used to study how the permanent incomes and employment states of individual workers evolve over time, the amount of worker turnover in excess of job reallocation, the lengths of job tenures and unemployment durations, and the size and persistence of changes in workers’ incomes following displacements or job‐to‐job transitions.